Perancangan Sistem Pembangkit Listrik Tenaga Picohydro Head 0,7m pada Aplikasi Kebutuhan Pertanian di Desa Indragiri - Dede Tria Ferdian; Muhammad Wildan Yusuf; Nugraha, Noviyanti; Ridwan, Muhammad (Jurnal Teknik Mesin Sinergi, 2026)
Limited electricity supply in crop storage buildings in Indragiri Village necessitates a simple alternative energy system that is suitable for local irrigation flow conditions. With a discharge of 0.006 m³/s and a head of 0.7 m, this study designed a picohydro power generation system through an engineering design approach that included energy requirement analysis, turbine component calculations, and mechanical design. The Pelton turbine was selected due to its optimal performance at low flow rates and its easy-to-maintain construction. The design results indicate a theoretical power of 28 Watts. The main components include a galvanized hollow frame measuring 850 × 500 × 350 mm, a runner with a diameter of 457.2 mm, a shaft with a diameter of 26 mm, blades measuring 150 × 100 × 50 mm, and pulleys measuring 304.8 mm and 50.8 mm. Materials such as chrome steel, resin, and aluminum were selected to ensure mechanical strength and corrosion resistance. This picohydro system is considered suitable as a small-scale alternative energy source for lighting and light electronic devices in agricultural facilities, and has the potential to be applied as a sustainable energy solution in Indragiri Village.